CELEBRITY INFLUENCE AND ADVERTISEMENT EFFECTIVENESS: HOW CHA EUN WOO AFFECTS PURCHASE DECISIONS FOR WALL’S CORNETTO WHITE ROSE - Roudlotul Auwalina; Rizky Eka Febriansah; Dewi Komala Sari (Journal of Artificial Intelligence and Digital Economy, 2024)
General Background: The influence of marketing strategies on consumer purchasing decisions is a key area of research, particularly in the context of popular culture endorsements. Specific Background: This study explores the impact of celebrity worship, brand ambassadors, and advertisements on the purchasing decisions for Wall's Cornetto White Rose ice cream among K-Pop fans in Sidoarjo. Knowledge Gap: While existing research highlights the effects of these marketing elements individually, there is limited evidence on their combined impact in the specific context of K-Pop endorsements. Aims: The aim of this research is to quantitatively assess how celebrity worship, the role of brand ambassadors, and advertisement effectiveness influence consumer purchase decisions for Wall's Cornetto White Rose ice cream. Results: Utilizing a descriptive quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0, the study finds that while celebrity worship and advertisements significantly influence purchase decisions, the presence of a brand ambassador does not. The results show that celebrity worship and advertisements positively impact consumer choices, whereas the brand ambassador's role is not a determining factor. Novelty: This study provides new insights into the relative importance of celebrity worship versus brand ambassador influence, specifically within the K-Pop fan segment. Implications: The findings suggest that marketers should focus on enhancing celebrity-driven campaigns and effective advertisements to influence purchasing decisions, rather than overemphasizing brand ambassadors. Limitations include the study's focus on K-Pop enthusiasts, which may not generalize to other demographics, and the use of Google Forms for data collection, which could affect response quality. Future research should consider a broader audience and direct survey methods for more comprehensive results.